Nutritional responses on the hypothalamic-pituitary-ovarian axis on female goats - Shikh Maidin, Mashitah (UB Press, 2016)
Livestock production efficiency depends greatly on nutritional management for reproductive efficiency (‘focus feeding‘), as embodied in the concept of ‘clean, green and ethical management‘. As reported in sheep studies, changes in the levels of nutrition primarily affect a range of blood-borne metabolic factors that appear to exert direct and indirect effects on reproductive performance through actions on the hypothalamic-pituitary-ovarian axis. The similarities between sheep and goats in their basic reproductive biology suggest that the same responses would be seen in female goats. However, there has been little experimentation in goats compared to sheep, so we know almost nothing for goats about the effects of nutritional supplements on the feed-forward-feedback loops in either the reproductive axis or the metabolic homeostatic systems. Thus, it is important to understand the fundamental of reproductive physiology that could alter the reproductive performances in goats.